1999
DOI: 10.1002/(sici)1096-9918(199912)27:12<1064::aid-sia676>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk composition of lithium manganese oxides

Abstract: Lithium manganese oxides, and in particular the spinel-structured LiMn 2 O 4 , have been investigated as potential active cathode materials for lithium ion batteries. Recently both orthorhombic and monoclinic LiMnO 2 have attracted considerable attention. It has been reported that Al doping allows the preparation of monoclinic LiAl x Mn 1−x O 2 under suitable reaction conditions, and furthermore improves the capacity retention of both o-LiAl x Mn 1−x O 2 and m-LiAl x Mn 1−x O 2 . The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 22 publications
6
18
0
1
Order By: Relevance
“…To identify the valence state of Mn and Ni in the pristine Li 1.87 Mn 0.94 Ni 0.19 O 3 composite, X‐ray photoelectron spectrometry (XPS) was performed and the spectra of Mn‐ and Ni‐2p is shown in Figure b,c. The Mn 2p 3/2 binding energy is around 642.2 eV, which is consistent with that of Mn 4+ . Generally, the Ni 2p 3/2 energy in XPS is around 854 eV for Ni 2+ and 856 eV for Ni 3+ .…”
Section: Resultssupporting
confidence: 72%
“…To identify the valence state of Mn and Ni in the pristine Li 1.87 Mn 0.94 Ni 0.19 O 3 composite, X‐ray photoelectron spectrometry (XPS) was performed and the spectra of Mn‐ and Ni‐2p is shown in Figure b,c. The Mn 2p 3/2 binding energy is around 642.2 eV, which is consistent with that of Mn 4+ . Generally, the Ni 2p 3/2 energy in XPS is around 854 eV for Ni 2+ and 856 eV for Ni 3+ .…”
Section: Resultssupporting
confidence: 72%
“…species [55], indicating the majority presence of Mn 2+ in the bioactive glass structure. In fact, previous works have shown that oxidation states such as +4 and +7 are unlikely in silicate systems and that this ion is normally present as Mn 2+ in these structures, although Mn 3+ can also be observed, shifting the Mn 2p bands to higher binding energy values [56][57][58]. The spectra also showed similar shape and Mn 2p position, indicating that even after incorporation of different Mn contents on the glass structure, the Mn chemical environment was maintained.…”
Section: Structural Evaluationmentioning
confidence: 81%
“…S2 †). 33,34 The main peak remains almost unchanged on the charging to 4.8 V (Sps. #2-6), indicating that the tetravalent Mn ions have no contributions to charge compensation on the initial charging process.…”
Section: Methodsmentioning
confidence: 99%